Dinuclear cadmium indomethacin and Lawsone complexes: synthesis, crystal structures, antiproliferative and biological evaluations. Issue 20 (17th October 2016) - Tabrizi, Leila; Golbang, Reza; Sadeghi, Hamid; Chiniforoshan, Hossein; Mcardle, Patrick; Notash, Behrouz
Abstract: The synthesis and structural characterizations of Cd(II) indomethacin (Indo) and Lawsone (Law) complexes, K2 [Cd2 (Indo)4 (SCN)2 ], 1 and [Cd2 (Law)4 (phen)2 ]·4CH3 OH, 2 (SCN = thiocyanate, phen = 1, 10-phenanthroline), have been studied. The complexes are dimeric, structurally characterized by spectral (IR, TOF-Mass) and X-ray crystallography. The interaction of indomethacin and Lawsone ligands, 1 and2 with calf thymus DNA and bovine serum albumin were investigated using UV–visible and fluorescence spectrophotometric methods. The in vitro cytotoxicity of1 and2 was examined against promyelocytic leukemia (HL-60), colon (HCT-8), brain (SF-295), and melanoma (MDA-MB-435) cancer cell lines. Moreover, the antimicrobial activity of1 and2 against different strains of pathogenic bacteria were tested. Abstract :